PANTUN ANTARBARANG DALAM UPACARA PERKAWINAN MASYARAKAT MELAYU PONTIANAK - Ristina, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This thesis is motivated by an interest researchers know about the meaning, function, and the use of language in rhyme antarbarang in Pontianak Malay community marriage ceremony. Subproblems this study were 1) how to function in a marriage ceremony rhyme antarbarang Pontianak Malay society, 2) how the themes and rema contained in rhyme antarbarang in Pontianak Malay community marriage ceremony. The method used is descriptive method with a form of qualitative research. The approach used is functional linguistics linguistics. Based on the research of the poem antarbarang in Pontianak Malay community marriage ceremony of 50 data poem there are three functions in rhyme antarbarang namely ideational function, interpersonal function and textual function. Ideational functions present in 50 of the 50 data rhyme rhyme. Interpersonal function present in 26 of the 50 data rhyme rhyme. While the textual functions found on 50 of the 50 data rhyme rhyme. Scene 50 data contained in the poem is the theme of textual, interpersonal themes and topical theme. Rema as explanatory sentence that follows the theme of the data contained in each poem. Â Keywords: rhyme, function, theme, rema.